Pengaruh Kreativitas Mengajar dan Fasilitas Pembelajaran Terhadap Prestasi Belajar Siswa Kelas VIII Mata Pelajaran IPS Di Sekolah Menengah Pertama Teknologi Pilar Bangsa Sepatan Tahun Ajaran 2018/2019 - Annisa Fitri Arifin; Femi Handayani; Agus Suherman (Universitas Islam Syekh Yusuf, 2020)
ABSTRAKThis research uses quantitative research methods with data analysis techniques using multiple regression techniques. The population in this study were students of class VIII at the Pilar Bangsa Sepatan Technology Middle School and the samples taken were all students of class VIII, namely 85 students. The instrument collects data for teaching creativity (X1), learning facilities (X2) and learning achievement using a questionnaire / questionnaire with a Likert scale of 5 (five) alternative answers. Based on the results of calculations this study proves that the partial variables of teaching creativity and learning are positive and significant for student learning achievement. Likewise, simultaneous testing that is approved for teaching creativity variables and learning facilities is positively and significantly related. so, it can be concluded from the level of motivation and compensation to improve teacher performance both simultaneously and partially.